Translating climate-smart agriculture policies into action: A guidebook for operationalizing climate-smart agriculture into local action planning - Girvetz, Evan Hartunian; Ndetu, Veronica; Mwongera, Caroline; Lamanna, Christine; Kamau, Hannah N.; Kinyua, Ivy Wambui; Ogwang, Vincent; Mbae, Robin; Kibor, Benjamin T. (2021)
Various countries have made significant progress in translating climate ambition into national action through legislation and policies addressing adaptation and mitigation. There is, however, a gap in the translation of national policies into local actions. Bridging this divide requires developing the capacity of technical officers and policymakers at multiple scales, including at the subnational and local community levels, to facilitate effective policy implementation. We organized sensitization and capacity-building workshops for subnational agricultural officers in Kenya against this backdrop. This guidebook details lessons and activities that will result in completed templates for CSA action plans or project concepts.